Study of the applicability of the hybrid management method in technology and innovation projects in a steel factory - Santos, Rayane Freire; Frossard, Gabriela Corrêa; Gomes , Kívia Carolina Fonseca Campos; Pereira, Natália Fernanda Santos (Brazilian Journal of Production Engineering, 2024)
Technology and innovation projects face increasing complexity in the dynamic context of digital transformation. To deal with this challenge, organizations are looking for more flexible project management models capable of managing the constant changes in this environment. This study examines how a steel company balances traditional and agile project management practices while developing technology projects. The study is based on reviewing the literature, project management topics and structuring the hybrid management model. The methodology used was qualitative research, described by its applied nature. A Case Study was carried out to elucidate critical points of the proposed discussion. The scientific contribution of this study lies in its ability to demonstrate how organizations can adapt to the dynamic environment of digital transformation by employing hybrid approaches. The results obtained during the research are presented, highlighting how flexibility and adaptability are relevant to dealing with the environment's complexities and how less predictability in deadlines and continuous dependence on communication indicate the need for constant attention. Finally, it is concluded that a hybrid methodology is necessary to deal with projects that involve technology and innovation.
Keywords: Project management; Technological innovation; Scrum